ELECTRICAL PROPERTIES OF GNEISSES IN THE UKRAINIAN SHIELD UNDER HIGH THERMOBARIC CONDITIONS - Lebedev T.S.; Shepel S.I. (My University, 2001)
Thermobaric variation of electrical characteristics of sets of different gneisses from the Central Ukrainian Precambrian Shield were studied. Experiments were carried out on dry, air-dried and fluid-saturated samples at different temperatures (T) (high temperatures included) and pressures (P). Analysis of mean values of the electrical parameters studied showed that pyroxene-biotite gneisses had the lowest electrical resistivity. On the other hand, their dielectic coefficient ε was highest. This regularity can be explained by pyroxene-biotite gneisses being greatly affected by secondary transformations. The result was serpentinization of plagioclase and development of chlorites and amphiboles among dark-coloured minerals. The above processes caused additional defect domains to appear in the crystalline lattices of minerals. The latter reduced the activation energy (E) of current-carriers and resistivity (ρ). It was established that ρ of gneisses decreases from the dry to the water-saturated state. That transition is especially significant in high-resistivity gneisses. As mineralisation increases from 0.1 to 100 g/1, ρ decreases by an average of ≈1.5 orders of magnitude. Given the same concentration range of the salts with which the solutions are saturated, the ε increase rate is greatest in the low-frequency range. A relatively clear-cut relationship between porosity and electrical properties was established for gneisses. It was shown that ρ of water-saturated gneisses decreases when porosity increases, while their ε increases simultaneously. Moreover, the difference between the absolute ε and ρ values of potentially gold-productive and unproductive strata of this region, established under atmospheric PT conditions, persists at high temperatures. Studies of the variation of electrical resistivity in dry, air-dried and water-saturated gneisses under high temperature and quasi-hydrostatic pressure, simultaneously applied, showed that it depended considerably on water content. The increase of quasi-hydrostatic pressure reduces E and the transition temperature from extrinsic to intrinsic conductivity significantly. On the basis of system analysis of experimental data obtained, as well as on the data of P and T distribution in the Earth's crust of the Central Ukrainian Shield and the probable depth of occurence of gneisses, electrical resistivity values were predicted down to 15 km depth.
Keywords: Precambrian; Precambrian; Докембрий